2015
DOI: 10.15835/buasvmcn-hort:11091
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of cultivar, rootstock and culture system on growth and yield in apple

Abstract: The influence of two apple rootstocks (M9 and MM106) on growth and yielding of four apple cultivars ("Pinova"‚ "Topaz", "Florina" and "Golden Reinders") in two culture system was studied. The experiment was placed in a commercial orchard at SC Agroindustriala Cluj-Napoca Romania, planted in 2007, during 2012-2104. In the experimental field some growth parameters (length of annual shoots, trunk cross-sectional area, tree height) and fructification (average yield and productivity index) were observed. The studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Apple rootstocks regulate tree growth, precocity, water and nutrient uptake and transport (Koepke and Dhigra, 2013;Kviklys et al, 2014). The rootstock has far more effect on the ultimate size of the tree than the scion cultivar (Tromp et al, 2005;Badiu et al, 2014). In agreement with this, Roy and George (1987) revealed that, rootstocks profoundly affect water and nutrients uptake from the soil especially nitrogen which is of prime importance as it affects the photosynthetic rate, production of carbohydrates and proteins, which in turn control plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Apple rootstocks regulate tree growth, precocity, water and nutrient uptake and transport (Koepke and Dhigra, 2013;Kviklys et al, 2014). The rootstock has far more effect on the ultimate size of the tree than the scion cultivar (Tromp et al, 2005;Badiu et al, 2014). In agreement with this, Roy and George (1987) revealed that, rootstocks profoundly affect water and nutrients uptake from the soil especially nitrogen which is of prime importance as it affects the photosynthetic rate, production of carbohydrates and proteins, which in turn control plant growth and development.…”
Section: Introductionmentioning
confidence: 99%